Mode stresses for the interaction between straight and curved cracks problem in plane elasticity - Aridi, Mohd Radzi; Nik Long, Nik Mohd Asri; Eshkuvatov, Zainidin K. (Scientific Research Publishing, 2014)
In this paper, the complex variable function method is used to obtain the hypersingular integral equations for the interaction between straight and curved cracks problem in plane elasticity. The curved length coordinate method and suitable quadrature rule are used to solve the integrals for the unknown function, which are later used to evaluate the stress intensity factor, SIF. Three types of stress modes are presented for the numerical results.